Soil Development and Land Suitability for Cacao on Sandstone and Pumice Breccia in the Semilir Formation in Ponjong District, Gunungkidul Regency, Indonesia - Candani, Dewi Madu; M. Nurcholis (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2024)
The parent material of the Semilir Formation, which consists of breccia pumice and sandstone, was located in the villages of Sawahan and Umbulrejo, Ponjong district, and it influences the genesis and soil types. This study utilized survey and laboratory analysis methods. Two soil profiles were studied: the first profile was located in Sawahan Village with breccia pumice as the parent material, while the second profile was in Umbulrejo Village with sandstone as the parent material. The research results indicated that soils developed from breccia pumice had diagnostic horizons of umbric epipedon and argillic endopedon with an advanced soil development stage. Soils developed from sandstone had diagnostic horizons of umbric epipedon and cambic endopedon with a young soil development stage. This affects the chemical properties of the soil. Soils formed from pumice breccia tend to have base saturation of less than 50% with low exchangeable bases, while soils formed from sandstone have base saturation of >50% with high exchangeable bases. Soils developed from breccia pumice and sandstone have soil classification as Typic Paleudults and Typic Dystrudepts. These soil types are suitable for cocoa plant cultivation; however, they require mechanical conservation through terrace construction and improved drainage by incorporating organic materials or compost into the soil, which can significantly enhance soil porosity, enabling better water retention and drainage.